PENGARUH KINERJA LINGKUNGAN DAN GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN: STUDI KASUS PADA SEKTOR ANEKA INDUSTRI DAN SEKTOR INDUSTRI BARANG KONSUMSI PADA PERUSAHAAN BURSA EFEK INDONESIA 2021-2024 - Sutisna, Sutisna; Sri Utami, Endang (Penerbit Lafadz Jaya, 2025)
This study examines the effect of environmental performance (PROPER score) and green accounting (disclosure dummy) on financial performance (ROA) of 42 companies in miscellaneous industry and consumer goods sectors listed on the Indonesia Stock Exchange (BEI) for 2021-2024 (168 observations). Using multiple linear regression with complete classical assumption tests (SPSS 26), results show environmental performance significantly positively affects ROA (β=1.284; t=4.115; p<0.01), while green accounting is insignificant (β=0.856; t=1.643; p=0.102). Simultaneously, both explain 45.2% of ROA variation (F=68.34; p<0.01). Findings support Dowling & Pfeffer's (1975) legitimacy theory: Gold/Green PROPER firms achieve 3.8% higher ROA through energy efficiency and ESG investor preference. Green accounting remains ineffective due to superficial disclosure (42% GRI 300 items). Implications: managers prioritize PROPER (128% ROI/point); regulators mandate sustainability reporting assurance. Limitations: two BEI sectors. Suggestions: size moderation test, mining replication.